2023
DOI: 10.1111/ctr.14924
|View full text |Cite
|
Sign up to set email alerts
|

Variation in adult living donor liver transplantation in the United States: Identifying opportunities for increased utilization

Abstract: In the United States, living donor liver transplantation (LDLT) is limited to transplant centers with specific experience. However, the impact of recipient characteristics on procedure selection (LDLT vs. deceased donor liver transplant [DDLT]) within these centers has not been described. Transplant registry data for centers that performed ≥1 LDLT in 2002–2019 were analyzed using hierarchal regression modeling to quantify the impact of patient and center factors on the adjusted odds ratio (aOR) of LDLT (vs DDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Workgroup 1 was tasked with (1) developing and disseminating a pre-conference survey to liver transplantation centers across the US assessing attitudes toward LDLT, and barriers to and facilitators of LDLT utilization and expansion; and (2) examining national transplant registry data to describe the epidemiology of US LDLT and to identify variation in access to LDLT across centers and patient groups that may inform strategies for reducing access disparities. 20,21 The six other workgroups focused on selected domains encompassing the entire process of LDLT. The conference roster is provided in Responses were based upon a nine-point scale, ranging from 1 = Unimportant to 9 = Very Important.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Workgroup 1 was tasked with (1) developing and disseminating a pre-conference survey to liver transplantation centers across the US assessing attitudes toward LDLT, and barriers to and facilitators of LDLT utilization and expansion; and (2) examining national transplant registry data to describe the epidemiology of US LDLT and to identify variation in access to LDLT across centers and patient groups that may inform strategies for reducing access disparities. 20,21 The six other workgroups focused on selected domains encompassing the entire process of LDLT. The conference roster is provided in Responses were based upon a nine-point scale, ranging from 1 = Unimportant to 9 = Very Important.…”
Section: Methodsmentioning
confidence: 99%
“…20 Secondly, an analysis of national transplant registry data was conducted and demonstrated that liver transplant candidate access to LDLT varies across transplant centers, and with patient factors correlated with access that include both social determinants of health and clinical characteristics. 21 As outlined in Figure 1, data from both were presented at the start of the consensus conference meeting.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In addition to harming donors directly, these costs pose financial barriers to living donation that reduce the number of available donors, particularly those whose potential recipients have sociodemographic characteristics associated with disparities in access to living donor transplantation. 2,5 Several pathways to achieving financial neutrality for living donors require increased support to fulfill their intended goals (Figure 1). 6 One straightforward mechanism of eliminating the direct costs incurred by living donors is prepayment or reimbursement by government-or transplant system-funded entities.…”
mentioning
confidence: 99%